Adad [Antonyms] and Its Impact on the Exegesis of Al-Samin in His Books (Al-Durr) And (Al-’Umda) - Rayan , Dr. Ayman Ibrahim Yusuf (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
This research tackles the subject of the indication of antonyms and its impact on the exegesis of al-Samin in both his books “al-Durr al-Masun” (Preserved Pearls) and “‘Umdat al-Hufaz” (Reliance of the memorize-rs). In this research, I have combined between the language and tafsir (exegesis) and clarified the efforts exerted by al-Samin in serving the interpretation of the Quran. Moreover, I have introduced his great contribution to linguistic research and compiled the conclusions he has reached in both his books (al-Durr) and (al-’Umda) on antonyms. I have organized his ideas, studied his tangible effects in his exegesis of the holy Quran in addition to methodologically establishing the role of the language being one of the tools in the past and contemporary exegesis of the holy Quran and clarified its multiple indications and various manners. I was also keen in highlighting the importance of the indication of antonyms and the extent of its impact on interpreting the noble Quran. Moreover, I have studied the points of contention among the scholars and exegists on the meaning of the Quranic statement and clarified the importance of the Quranic context in determining the exact meaning of the vocabularies and structures. Furthermore, I have highlighted the close connection between the developed indication of words and the intended meaning in the Quranic verse.